Chapter Il ‘distacco’ dalla famiglia d’origine. Concepire la rinascita in età adulta - STRAMAGLIA, Massimiliano (Firenze University Press, 2023)
Adulthood, once defined as a goal, today, has increasingly blurred outlines. While many speak of "adultescenza" (adult-adolescent) to describe the situation of those who interpret their adulthood in adolescent terms, today, we have, in one way, less certainty, in another way, more possibilities. For example, social sciences assign adolescents the task of choosing, where reality confirms that the choices taken in adolescence are not "for life," but circumstantial. Adolescents, rather, discover; adults rediscover. Thus, in adulthood, a detachment from the family of origin can take place which in adolescence was thought inconceivable: freedom, autonomy and responsibility can finally be considered adult goals, because the family of origin sometimes still has to-be-thought-of.